Influence of Human Resources, Information Technology, and Legal Regulations on the Timeliness of Output Achievement Reporting (Case Study on Work Units within the KPPN Yogyakarta) - Khatarine, Rendhita Dizzy; Candra, Yudas Tadius Andi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the influence of the variables of human resources, information technology, and legal regulations on the timeliness of output reporting in work units within the KPPN Yogyakarta. The approach used in this research is a quantitative approach with a causal relationship method. Data is collected through questionnaires, and the method employed is purposive sampling with multiple linear regression analysis. A total of 42 respondents are gathered. The results indicate that the variables of human resources, information technology, and legal regulations have a positive impact on the timeliness of output reporting.